Economics and environmental-health risk assessment for sustainable development of the gold mining industry in Nigeria (2024)
Though the gold mining industry potentially generates employment and increases Nigeria’s foreign exchange, the crude practices of artisanal miners often exacerbate environmental degradation and health hazards. Hence, humans face health risks when excessively exposed to the heavy metals released during gold mineralization. This study, therefore, adopts a descriptive approach towards suggesting a comprehensive economic evaluation and risk analysis for managing the impact of gold mining industry sustainably and bearing in mind people’s health that should equally be managed in a healthy and sustainable manner. A review of existing Environment-Health Risk Assessment (EHRA) studies on gold mining areas in Nigeria reveals that the estimated risk quotients are generally above recommended limits consequent upon inadequate enforcement of mining precautions. This study, therefore, argues that incorporating EHRA studies and considering economic costs and benefits of mining could provide an objective benchmark for managing various estimated health risk quotients and returns from more gold mining. For Nigeria’s, harnessing opportunities in the gold mining industry requires interdisciplinary drive that seeks to incorporate environmental-health risks into optimization of gold mining industry. Appropriate policy interventions will be expedient for gold mining industry to be less harmful and not constitute direct threat to sustainable development in Nigeria.